+0  
 
+1
191
2
avatar+1117 

This is the one I couldn't figure out

 

(x + 1)^2 = (x + 1) (x + 1)

 May 14, 2019
edited by SmartMathMan  May 14, 2019
edited by SmartMathMan  May 14, 2019
 #1
avatar+8852 
+3

(x + 1)2   =   (x + 1)(x + 1)

 

Multiply each item in the first set of parenthesees by each item in the second set of parenthesees.

 

(x + 1)(x + 1)   =   (x)(x) + (x)(1) + (1)(x) + (1)(1)

 

Simplify.

 

(x)(x) + (x)(1) + (1)(x) + (1)(1)   =   x2 + 2x + 1

 

So....

 

(x + 1)2   =   x2 + 2x + 1

 May 14, 2019

22 Online Users

avatar